Older adults' experiences of maintaining social participation: Creating opportunities and striving to adapt to changing situations. (3rd October 2022) - Löfgren, Maria; Larsson, Ellinor; Isaksson, Gunilla; Nyman, Anneli
Abstract: Background: Social participation concerns the possibility of engaging in activities in interaction with others or society at large and contributes to the health and well-being of older adults. In contrast, a lack of social participation is associated with loneliness. It is, therefore, important to understand what strategies older adults use to maintain social participation. Aim: To explore and describe older adults' experiences of maintaining social participation. Materials and methods: Nine older adults, aged 69–92 years, participated in interviews that were analysed through qualitative content analysis. Results: The overall findings reflect how older adults create opportunities for social participation by developing strategies and striving to adapt to changing situations, emphasizing how maintaining social participation is an active process. Preserving social participation requires motivation and an effort to take initiative to cultivate social relations, maintain community bonds, engage in social events and activities and stay connected with society. Conclusions and significance: These results may extend our understanding of strategies that older adults use, as well as the challenges they face when striving to adapt to new circumstances. This study may have implications for the practice of how to support older adults' social participation.